Jerusalem, Israel/Palästina: Das Projekt „Geophysikalische Erkundung der Lage und des Verlaufs der herodianischen Stadtmauer unter dem heutigen christlichen Viertel der Jerusalemer Altstadt“ - zu Löwenstein, Sophie (e-Forschungsberichte des DAI, 2023)
The project aims to find traces of the Herodian city wall (‘Second Wall’) in Jerusalem. As Flavius Josephus mentioned (Bell. V 4,2 § 146), the wall started at the „Gennat Gate“ and ran to the fortress “Antonia”. After the Jewish rebellion it has been destroyed by Titus in 70 AD. The ‘Second Wall’ could not be found yet. But the course of this Herodian city wall has some importance for the location of Golgotha and has therefore been discussed for more than 150 years. Since there is no possibility to undertake new excavations within the Old City the project uses geophysical methods. Within two seasons (2015 and 2016) the 7 m deep sondage underneath the Church of the Redeemer as well as several places in the Muristan, the Suqs and of the ‘Via Dolorosa’ will be measured. The first season took place in September 2015 and was a pilot study in order to proof the geographical and local measurement conditions and to solve the technical challenges given by the deep and narrow sondage underneath the Church of the Redeemer. Until October 2016 a high sensitive device has to be developed for measurements.